Avaliação do grau de implementação da assistência à pessoa com diabetes mellitus na Saúde da Família no município de Cuiabá-MT : um estudo de caso - Borges, Rita Christina Martins (2013)
The Diabetes Mellitus throuth years has become a great public health problem. During the year of 2001 the Ministry of Health launched the Attencion Plan Reorganization to the Arterial Hipertension and Diabetes Mellitus with the objective of reorganize the assistence provided to these patologies. According to this plan the Basic Attention (AB), specifically the Family Health Strategy (ESF) should be the responsible to the attendence and treatment of the peolple with diabetes. Considering the several potenciality of the evaluation use, mainly to a better future actions to be developed, this research evaluated the degree of the deployment assistance given to a diabetic person envolving two units of Fmalily Health in the city of Cuiabá-MT. It is a evaluative research where political and organizational contexts were considered order to evaluate the deployment assistance to the diabetic person. Were built: the logical pattern of assistence to the diabeteic person. Were built: the logical pattern of assistence to a diabetic person and also a theorical pattern of evaluation with the objectie of subsidize the evaluation. The methodological approach chosen was the study of the case, the units of ESF researched obeyed the creiteria previewsly stabilished. In the dada collection were used primary and secondary data. The evidence demostrated by the data collection instruments were transported to the information/relevance matrices, emphasized by the specialists that later resulted in the matrix of analysis/judgement whre evaluated the degree of the implementation. The results of this study to the assistence of diabetic person are the following: in the political context it reached 22,44% considering a critical classification in the assistence where are included the necessary resources for the organization staff, the recommended activities in order to assist the diabetic person and the numbers of attendances realized for Santa Izabel III staff, the result were of the 38,11% for Family Health staff and 34,73% for the Jardim Vitória I staff. The degree of deployment founded were a critical deployment in the assistence to a diabetic person for both staff.